Psychometric and Neurophysiological Assessment of School Children with Attention Deficit Hyperactivity Disorder-Toward Better Management and Treatment - Pop-Jordanova N; Zorcec, Tatjana (SHMSHM / AAMD, 2017)
ADHD represents a big problem in the educational process because these children are not able to be attentive, patient, to seat quietly during the class, and additionally they have learning difficulties. In the past decade researchers became more involved in defining and evaluating executive functions in children manifesting Attention Deficit Hyperactivity Disorder (ADHD). Executive functions are involving information from the working memory, inhibition of the inappropriate behavior, as well as directing and sustaining the attention, towards a goal-oriented behavior. The aim of this article is to show our results obtained from psychometric and neuropsychological evaluation of the executive functions in a group of school children diagnosed as ADHD, as well as results for neurofeedback training we used therapeutically. The evaluated group is composed of 50 ADHD children and 20 healthy children as a control, matched by age and gender. Neurophysiological assessment was performed with Visual Continuous Performance Test (VCPT) from which Event Related Potentials were extracted. Psychological assessment comprised the use of Stroop Color Word Task (SCWT) and Wisconsin Card Sorting Test (WCST), while mothers fulfilled Child Behavior Check List (CBCL) and ADD-H: Comprehensive Parent Rating Scale (ACTeRS). Obtained results from psychological and neurophysiological assessment confirmed the diagnosis of ADHD as well as a presence of serious difficulties in executive system functioning trough ERP’s component extracted from QEEG analysis. As a used nonpharmacological therapeutic approach we accentuated very positive outcome of neurofeedback treatment of these children.
Keywords: ADHD; children; executive functions; neuropsychological assessment